Studi Meta-Analisis: Faktor Sosial-Psikolog (Peran Dukungan Suami) dalam Pengambilan Keputusan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Mitha Farihatus Safiroh; Nunik Puspitasari (Media Gizi Kesmas, 2023)
Background: KB (Keluarga Berencan) is a program of efforts to regulate the birth of children, the ideal distance of birth and ideal age to have birth, to regulate pregnancy, through promotion, protection, and assistance in accordance with reproductive rights to create a quality family. The known family planning programs are traditional KB and modern KB, usually in the form of hormones. BKKBN seeks to achieve the target of modern family planning services in Indonesia, one of which is the Long-Term Contraception Method (MKJP) for a mother (wife) consisting of KB Implants/implants, IUD, and MOW. In deciding to carry out MKJP a mother (wife) the form of the husband's support role is needed both mentally and materially (economically) to support it. Objective: The purpose of this study is to analyze the role of husband's support in decision making on the use of Long Term Contraception Methods (MKJP) in Indonesia.Methods: The method used in this study is to use Meta-Analysis by reviewing 24 journals that have been published. Discussion: Through a meta-analysis in this scientific article journal, 24 articles were found that had the topic of husband's support for decision making using MKJP with a p-value of 0.002 < 0.005, so from 24 studies, it was explained that there is a husband's role in decision making and is significant with the magnitude of the effect. size is 0.3063 although it is classified as moderate in influence. Conclusion: Social-Psychological Factors (Role of family/husband support) in Decision Making on the Use of Long-Term Contraception Methods (MKJP), family or husbands play a role in influencing wives in making decisions to use KB (Family Planning) with Long-Term Contraception Methods (MKJP).